1998
DOI: 10.1002/etc.5620170914
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of endosulfan to aquatic stages of anuran amphibians

Abstract: Abstract-The toxicity of endosulfan insecticide to wood frog (Rana sylvatica) embryos and tadpoles of wood frogs, American toads (Bufo americanus), and green frogs (R. clamitans) was examined in the laboratory. Following exposures to 0.03 to 0.4 mg/L endosulfan for 96 h, sublethal effects and postexposure mortality were assessed. In another experiment, premetamorphic American toad tadpoles (with developing hindlimbs but unerupted front legs) were exposed to 0.3 mg/L endosulfan for 96 h. The exposed wood frog e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 26 publications
7
63
0
2
Order By: Relevance
“…Although kinorhynchs present their bodies covered by a strongly water-repelling cuticle (Giere, 2009), a fact that favors the passive uptake of pesticides, this group showed of the endosulfan applied through the Thiodan pesticide may have been degraded to endosulfan sulfate (unmeasured values). Both endosulfan isomers exhibited relatively short half-lives and the present results are consistent with other microcosm studies that reported significant losses of more than 50% in two weeks or even during the first days after the application of initial nominal concentrations (Guerin & Kennedy, 1992;Berrill et al 1998;DeLorenzo et al 1999). In addition, according to Laabs et al (2007), small microscosm systems ( < 1 L) have a low surface/volume ratio that favors endosulfan hydrolysis and losses by edge effects, fact also observed previously in the studies of Flemer et al (1995) and Barry & Logan (1998).…”
Section: Endosulfan Effects On Meiofauna Structuresupporting
confidence: 92%
“…Although kinorhynchs present their bodies covered by a strongly water-repelling cuticle (Giere, 2009), a fact that favors the passive uptake of pesticides, this group showed of the endosulfan applied through the Thiodan pesticide may have been degraded to endosulfan sulfate (unmeasured values). Both endosulfan isomers exhibited relatively short half-lives and the present results are consistent with other microcosm studies that reported significant losses of more than 50% in two weeks or even during the first days after the application of initial nominal concentrations (Guerin & Kennedy, 1992;Berrill et al 1998;DeLorenzo et al 1999). In addition, according to Laabs et al (2007), small microscosm systems ( < 1 L) have a low surface/volume ratio that favors endosulfan hydrolysis and losses by edge effects, fact also observed previously in the studies of Flemer et al (1995) and Barry & Logan (1998).…”
Section: Endosulfan Effects On Meiofauna Structuresupporting
confidence: 92%
“…This is consistent with Edginton et al (2004), who found that embryos (Gosner stage eight) of Xenopus laevis, Bufo americanus, Rana clamitans and Rana pipiens exposed to glyphosate formulated vision ® were less sensitive than larvae (Gosner stage 25). The greater sensitivity to pesticides of larval stage as compared with the embryonic stage of amphibians has been also reported by Hall and Swineford (1980), Berrill et al (1993), Berrill, Bertram, McGillivary, Kolohon and Pauli (1994), Berrill, Coulson, McGillivary and Pauli (1998), Edginton et al (2004). Surfactants have been demonstrated to cause lysis of gill epithelial cells in the rainbow trout (Partearroyo, Pilling, & Jones, 1991), and affect the ability of the gills to maintain osmotic balance.…”
Section: Discussionmentioning
confidence: 81%
“…Endosulfan, a mixture of a-and b-isomers, is a broad-spectrum insecticide, acaricide and miticide used to control a variety of pests that affect fruit, vegetables and ornamental plants (Berrill et al, 1998). This formulation with two isomers with different water solubilities and volatilities (Antonious et al, 1998) has been studied for its toxicity to aquatic organisms possibly affected by direct applications or drift from aerial spraying (Ernst et al, 1991;Berrill et al, 1998). Accumulated data concerning the toxicity hazard of endosulfan led to the recommendation that it should be replaced by less toxic alternatives wherever possible (Berril et al, 1998).…”
Section: Introductionmentioning
confidence: 99%